Analisis Model Prediksi Kebangkrutan Industri Garmen dengan Menggunakan Metode Altman Z- Score - Putro, Bramantiyo Eko; Pratama, Fajar (Jurnal Media Teknik dan Sistem Industri, 2017)
Abstract— PT. Eastern Modern Apparel is engaged in garment production. The company has experienced financial constraints. This is marked by the dismissal of some employees. Research is done to determine the prediction of bankruptcy of the company. Methodology that has been done in this research are conducting interviews with the company, field study, financial data retrieval. The step is done to meet the data needs in the next step. The next step is data processing using Altman Z-Score method. Processing consists of X1 = Working Capital Ratio against Total Assets, X2 = Retained Earnings Ratio against Total Assets, X3 = EBIT Ratio against Total Assets, X4 = Market Equity Value Threshold on Book Value of Debt. X5 = Sales to Total Assets. Processed data is in the period 2014, 2015, and 2016. The process produces Z-Score value for each period. Z-Score calculation results in the period 2014 = 3.91, 2015 = 3.19, and 2016 = 2.83. While the limits of healthy company according to calculations Almant Z-Score of> 2.675. Then the results of Altman Z-Score calculations on the company is said to be healthy, because the results exceed the limits of the healthy category. However there is a decrease of each period.Keywords: Corporate Financial Performance, Altman Z-Score, Healthy Company